Optimal support systems for patients with stomas – an opinion piece - Burch J (Dove Medical Press, 2014)
Jennie BurchSt Marks Hospital, Surgery, London, UKAbstract: Coping with a stoma is physically and emotionally difficult. This adaptation process can be hindered by various factors, including complications associated with the stoma, such as appliance leakage, and comorbidities, such as arthritis. There are many ways of learning to live successfully with a stoma, which may be influenced by family, health care professionals, and spiritual support. There is some evidence that a good social support network can result in a positive coping mechanism for people with a newly formed stoma. Difficulty in accepting the stoma has been shown to slow down the adaptation process. This article explores the basic issues related to stomas and the general preoperative and postoperative support that is supplied by health care professionals. There was no optimal support system protocol discovered in the review of the literature. However, some of the published data related to stoma care were extrapolated to enable the reader to understand the important role that support systems can play in the acceptance of the stoma. Health care professionals provide support in a variety of ways, including the provision of telephone advice, clinics, and “open days”, to assist the patient to come to terms with their newly formed stoma. Care includes training on the practical aspects of the stoma, supporting empowerment and self-efficacy of people with a stoma (ostomates), and providing assistance when problems arise. Other support systems that are available are support groups, which may be local or national. It can be seen that the adaptation process takes many months or longer, but by utilizing various means of support, people with a stoma can have a good quality of life. The optimal support systems for patients with a stoma are discussed in relation to the literature and the personal experience of the author.Keywords: colostomy, ileostomy, urostomy